RAMMED-EARTH ARCHITECTURAL HERITAGE IN HAVANA, CUBA: PRESENT AND PERSPECTIVES - Casal Iglesias, Francisco Tomas (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
Earthen constructions were the predominant typology in Havana in the 16th century, composed of simple earthen walls (earth deposited within a framework of sticks) or rammed earth, sometimes stabilized with lime and covered with guano (palm leaves) or tiles. The ive centuries, which have since elapsed, have minimized these typologies. Only inside the Historic Center of Old Havana, declared a World Heritage site, remain very old buildings with rammed-earth walls. The effects of climate change have had an adverse effect on the architectural and urban heritage, and have impacted negatively earthen construction, which is extremely vulnerable because of its fragility to looding, heavy rains and cyclonic winds (Casal, 2008). Moreover, given its small current representation in the city, these structures should be properly safeguarded. A study performed overlapped of the lowest-lying areas with different forecasts of weather events (tropical cyclones up to Force 5, combinations of extra tropical rainfalls and migratory anticyclones, cold fronts and the proper periphery of migratory anticyclones). This representation was intended to deine the damage area of the urban fabric near the coastline, which included Port Avenue and the old harbor, emphasizing the possible impacts on heritage and historic architecture. Conclusions and recommendations for further study are formulated, and additional preventive actions proposed, for diffusion among the community (Mitrani, 2006), in or der to safely protect valuable heritage of the lood-zone a rea of the Historic Center.